Analysis of Regional Financial Independence for the Implementation of Regional Autonomy in Palu City in 2015-2019 - Andi Herman Jaya (Jurnal Mantik, 2021)
This study aims to determine and analyze the level of regional financial independence in the context of implementing regional autonomy in Palu City in 2015-2019. Analysis of the data used in this study is the Regional Financial Independence Ratio. The results showed that the level of regional financial capability of Palu City which was calculated using the ratio of regional financial independence was declared unable to support the implementation of regional autonomy as indicated by the results of the data analysis of the Regional Financial Independence Ratio which was relatively low at 25.09 percent so that in the implementation of the government, Palu City was still require assistance from central and provincial government transfer funds.